Multimodal Imaging Guided Photothermal Therapy using Functionalized Graphene Nanosheets Anchored with Magnetic Nanoparticles - Yang, Kai; Hu, Lilei; Ma, Xingxing; Ye, Shuoqi; Cheng, Liang; Shi, Xiaoze; Li, Changhui; Li, Yonggang; Liu, Zhuang (Advanced materials (Weinheim), 2012)
In this work, a nanoscale reduced graphene oxide–iron oxide nanoparticle (RGO–IONP) complex is noncovalently functionalized with polyethylene glycol (PEG), obtaining a RGO–IONP–PEG nanocomposite with excellent physiological stability, strong NIR optical absorbance, and superparamagnetic properties. Using this theranostic nanoprobe, in‐vivo triple modal fluorescence, photoacoustic, and magnetic resonance imaging are carried out, uncovering high passive tumor targeting, which is further used for effective photothermal ablation of tumors in mice.